2023
DOI: 10.3390/f14050878
|View full text |Cite
|
Sign up to set email alerts
|

Community Abundance of Resprouting in Woody Plants Reflects Fire Return Time, Intensity, and Type

Abstract: Plants in fire-prone ecosystems have evolved a variety of mechanisms to resist or adapt to fire. Post-fire resprouting is a key adaptation that promotes rapid ecosystem recovery and hence has a major impact on the terrestrial carbon cycle. However, our understanding of how the incidence of resprouting varies in different fire regimes is largely qualitative. The increasing availability of plant trait data and plot-based species cover data provides an opportunity to quantify the relationships between fire-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…For both Shrubby Dry Forest and Sub-Alpine Woodland, there was no change in the relative frequency of fire response strategies in extant vegetation and the soil seed bank. This contrasts broader relationships for an increase in frequency in resprouting species with a shorter fire return interval, although such relationships are based on longer (>10 years) fire return intervals [128]. During high-severity fires, resprouters may be killed outright [123], and repeated, short-interval, high-severity fires may erode resprouting capacity due to a depletion in carbon reserves [63], as well as reducing benefits associated with carbon allocation to regrowth and meristem formation over seed production [128,129].…”
Section: Fire Frequency Effects On the Soil Seed Bank And Extant Vege...mentioning
confidence: 83%
See 1 more Smart Citation
“…For both Shrubby Dry Forest and Sub-Alpine Woodland, there was no change in the relative frequency of fire response strategies in extant vegetation and the soil seed bank. This contrasts broader relationships for an increase in frequency in resprouting species with a shorter fire return interval, although such relationships are based on longer (>10 years) fire return intervals [128]. During high-severity fires, resprouters may be killed outright [123], and repeated, short-interval, high-severity fires may erode resprouting capacity due to a depletion in carbon reserves [63], as well as reducing benefits associated with carbon allocation to regrowth and meristem formation over seed production [128,129].…”
Section: Fire Frequency Effects On the Soil Seed Bank And Extant Vege...mentioning
confidence: 83%
“…This contrasts broader relationships for an increase in frequency in resprouting species with a shorter fire return interval, although such relationships are based on longer (>10 years) fire return intervals [128]. During high-severity fires, resprouters may be killed outright [123], and repeated, short-interval, high-severity fires may erode resprouting capacity due to a depletion in carbon reserves [63], as well as reducing benefits associated with carbon allocation to regrowth and meristem formation over seed production [128,129]. Duivenvoorden et al [60] reported such a decline in clonal resprouters with an increase in the frequency of high-severity wildfires with a short (<10 years) return interval.…”
Section: Fire Frequency Effects On the Soil Seed Bank And Extant Vege...mentioning
confidence: 83%